2021
DOI: 10.1111/tpj.15567
|View full text |Cite
|
Sign up to set email alerts
|

Cell cycle checkpoint control in response to DNA damage by environmental stresses

Abstract: SUMMARY Being sessile organisms, plants are ubiquitously exposed to stresses that can affect the DNA replication process or cause DNA damage. To cope with these problems, plants utilize DNA damage response (DDR) pathways, consisting of both highly conserved and plant‐specific elements. As a part of this DDR, cell cycle checkpoint control mechanisms either pause the cell cycle, to allow DNA repair, or lead cells into differentiation or programmed cell death, to prevent the transmission of DNA errors in the orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 172 publications
(270 reference statements)
1
39
0
Order By: Relevance
“…Although the function of IGF2BP2 in thyroid cancer was totally based on the public database analysis and did not reveal the underlying mechanism of the role of IGF2BP2, they do indicate that IGF2BP2 is a gene worthy of further analysis to account for the pathophysiological process of thyroid cancer. Based on GESA analyses, high IGF2BP2 was positively correlated with several biological processes such as cell cycle, tight junction and focal adhesion, which were confirmed as being associated with cell differentiation in previous studies [21][22][23]. Inspiringly, we found that mPTC patients with high expression of IGF2BP2 benefitted less from 131 I treatment, indicating that such disease was apt to progress to RR-PTC, which was in line with findings of online database analyses.…”
Section: Discussionsupporting
confidence: 90%
“…Although the function of IGF2BP2 in thyroid cancer was totally based on the public database analysis and did not reveal the underlying mechanism of the role of IGF2BP2, they do indicate that IGF2BP2 is a gene worthy of further analysis to account for the pathophysiological process of thyroid cancer. Based on GESA analyses, high IGF2BP2 was positively correlated with several biological processes such as cell cycle, tight junction and focal adhesion, which were confirmed as being associated with cell differentiation in previous studies [21][22][23]. Inspiringly, we found that mPTC patients with high expression of IGF2BP2 benefitted less from 131 I treatment, indicating that such disease was apt to progress to RR-PTC, which was in line with findings of online database analyses.…”
Section: Discussionsupporting
confidence: 90%
“…As sessile organisms that are unable to escape from environmental hazards, plants utilize multiple pathways to cope with environmental stresses that can negatively affect DNA replication or cause DNA damage [ 10 , 11 , 51 , 52 , 53 , 54 ]. With its particular sensitivity to DNA damage induced by environmental stresses, the SCN has been shown to undergo cell death, thus protecting the genomic integrity and RAM activity to survive from severe stress [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Auxin efflux facilitators PIN-FORMED (PIN) family proteins generate and stabilize the auxin maximum and gradient, thus guiding root growth [ 8 ]. Being of a sessile nature, plants are continuously exposed to various environmental stress factors that can affect DNA replication or cause DNA damage [ 9 , 10 , 11 , 12 ]. Left unrepaired, DNA damage in actively dividing cells disrupts normal cellular functions and may thus severely affect plant growth and development [ 11 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, this network seems to be important for kernel developments in wheat. Furthermore, G2/M transition has an important role in plant tolerance in heavy metals tolerance (Francis 2011;Pedroza-Garcia et al 2022). Network 6 that control Manganese (Mn +2 ) transportation is very important in improving end-use quality.…”
Section: Gene Enrichment Biological Processes and Network Of Genes Co...mentioning
confidence: 99%